PENGARUH VARIASI UKURAN DIAMETER LUBANG MAGIC RING PADA EXHAUST MANIFOLD TERHADAP TORSI DAN DAYA SEPEDA MOTOR YAMAHA VEGA RR - Muhammad Mirwan Yazid; Ranto Ranto; Husin Bugis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
Vehicle performance will decrease with increasing age of use, it can be seen from the weakening initial torque and the power of the vehicle when driving unlike the initial production. Magic ring a tool produced by CV. SUMI INOTECH which utilizes the overlapping process of valves. The magic ring mounted on the header exhaust manifold serves to restore exhaust gas that is wasted from the overlapping process to return to the combustion chamber so as to produce more power to push the piston and the performance of the vehicle will increase. This study used an experimental method with the research object of Yamaha Vega RR in 2014. The magic ring used was the 16 mm magic ring serial number (ASJS032125) and the same magic ring but the inner diameter was enlarged to 18 mm. Using descriptive quantitative data analysis, it was found that the use of the magic ring added torque from the standard condition of 7.42% in the use of the 16 mm magic ring and increased by 7.12% in the use of the 18 mm magic ring. The power of the vehicle increased only 0.24% when using the magic ring 16 mm, and the use of the magic ring 18 mm power remained the same as the standard condition.